(untitled) (Studia Prawnicze / The Legal Studies, 1982)
The study is an attempt at linguistic analysis of verb indicators appearing in provisions of special part of the criminal code. To the class of verb indicators belong verbs denoting action. Semantic criterion for distinguishing this class is the reason of the fact that not only verbs but also verbal nouns and gerunds belong here. Verb indicators are verbs expressing action regardless of whether they denote an act in the form of action or omission. From grammatical point of view they appear in criminal code in present tense,. From semantic point of view these verbs in the criminal code have timeless meaning, i.e. they are neutral as regards the past, present and future. The above semantic feature is not specific for legal texts only, because in sentences characterized by grand qualifier analogous se- mantic function is fulfilled by present tense. Sometimes, verb indicators appear in criminal code in the past tense. This is, however, relative not absolute past tense. Its semantic function is to denote the relation of precedence as regards the moment indicated by other elements of the statement. Verb indicators appear in criminal code in their non-finite forms. Semantic function of this form depends upon whether we are dealing with the so called terminative or durative verbs. Besides, conjugation forms of present tense of the latter have a double meaning. They express both finite and non-finite forms. Semantic interpretation leads us to the conclusion that we should ascribe the meaning of the finite forms to verb indicators in criminal code. At the end of the study, the author discusses the issue of semantic functions of the so called durative and iterative verbs appearing in the criminal code.